Laparoscopic vs. open inguinal hernia repair: A systematic review of literature - Gupta, Amit; Jain, SK; Kumar, Sunil; Kaza, RCM (Asian Journal of Medical Sciences, 2014)
Inguinal hernia repair using mesh is one of the most frequently performed operations in general surgery. The mesh can be placed using an open technique or by laparoscopic approach. Many studies have highlighted the merits and risks of laparoscopic approach for the repair of inguinal hernia, the final sentence still remains to be written as majority of trials are too small to show clear benefits of one technique over another. To compare laparoscopic mesh repair with open method in management of inguinal hernia. Asian Journal of Medical Science, Volume-5(3) 2014: 11-14 DOI: http://dx.doi.org/10.3126/ajms.v5i3.9301